Influence of shared tasks in the quality of communication between executives and subordinates in private companies - Maguiña Rivero, Omar Fabricio (2021)
Objective: The objective is to determine the relationship between the shared tasks between the boss and the subordinates and the quality of communication in private companies. Method: The research was quantitative, non-experimental and correlational; the population taken into account were people belonging to the economically active employed population of the city of Trujillo in the year 2020. The sample was made up of 384 citizens of Trujillo, who belonged to the economically active employed population in the year 2020. Results: 43.0% of the surveyed workers present a high level of perception regarding the communication quality, and 62% estimate the common activities at a high level. Conclusion: The relationship between the shared tasks between the boss and the subordinates and the quality of communication was highly significative. A Spearman coefficient of (r = 0.619) at the level of p<0.01 was obtained; thus, it can be said that the higher the quality of communication, the better the development of common activities.